The relationship of physical activity and diet with obesity in State Junior High School 4 students in Malang City - Juanda, Syifa Ethika; Roesdiyanto, Roesdiyanto; Rahayuni, Kurniati; Widiawati, Prisca (CV. Media Digital Publikasi Indonesia, 2023)
Obesity is caused when calorie intake is greater than calories burned, causing the body to store unused calories in the form of fat. Physical activity is body movement caused by muscles. while diet is an attempt to regulate the amount and type of food. So the purpose of this study is to identify the correlation between physical activity and eating patterns with obesity in students of State Junior High School 4 Malang City. This study used a quantitative method, namely measuring height and weight in order to obtain a body mass index as a guideline for obesity classification. To find out the physical activity of the research respondents used the PAQ-A questionnaire, while eating patterns were assisted by a 24-hour Food Recall questionnaire. The sample in this study were 20 respondents who were obese at State Junior High School 4 Malang City. The results of the data analysis using the sperm correlation test showed that there was a significant relationship between physical activity (X1) and obesity (Y), namely Y = -047+021. There is a significant relationship between diet (X2) and obesity (Y), namely Y = 261+042. The results of multiple regression analysis showed that there was a significant relationship between physical activity and obesity, namely Y = 37.722 – 0.191 (X1) + 0.007 (X2). obesity variable of 0.007. Based on the t test, it was obtained tcount of physical activity of 675 and eating pattern of 167 with sig. <0.05, therefore reject H0 with the conclusion that physical activity variables and eating patterns have an effect.